Characterization and Field Performance of 15 Strawberry Germplasm under Bangladesh Conditions - Rahman, M Moshiur; Rahman, M Mizanur; Hossain, M Mofazzal; Mian, MA Khaleque; Khaliq, Q Abdul (SAARC Journal of Agriculture, 2014)
Fifteen strawberry germplasm collected from local and exotic sources were evaluated for different qualitative and quantitative characters. The germplasm showed variation for majority of the studied traits. Plant height during peak harvest ranged from 14.67 to 25.00 cm and FA 007 exhibited the tallest plants. The maximum number of leaves plant-1 was produced by FA 006 (46.67). The maximum number of runners plant-1 was obtained in FA 003 (68.67) followed by FA 004 (63.00), while the highest number of crown plant-1 was found in FA 007 (15.33) followed by FA 006 (14.67). Days to flowering varied from 48.33 to 102.30 among the germplasm and FA 008 required minimum (48.33) days for flowering. The germplasm FA 004 produced the highest number of flower trusses (35.50 plant-1) while it was the lowest in FA 010 (5.00 plant-1). The number of flowers plant-1 was found maximum in FA 003 (168.00 plant-1) and minimum in FA 010 (40.00 plant-1). Among the germplasm pollen viability varied significantly and maximum viable pollen was recorded in FA 010 (84 %), while it was lowest in FA 004 (12.00 %). The highest per cent fruit set was recorded in BARI Strawberry-1 (86 %) while, FA 013 (39 %) showed the lowest. Among the germplasm the highest yield plant-1 was recorded from FA 005 (737.70 g) followed by FA 006 (702.30 g) and was significantly higher than others while the lowest yield plant-1 was recorded from FA 013 (52.00 g), FA 014 (69.00 g), FA 009 (81.33 g) and FA 010 (121.30 g). DOI: http://dx.doi.org/10.3329/sja.v11i2.18404 SAARC J. Agri., 11(2): 81-94 (2013)